¿Contribuye la tecnología a la democratización financiera? La economía colaborativa y las fintech como catalizadoras del cambio - Rühl, Alexander; Palomo Zurdo, Ricardo (REVESCO. Revista de Estudios Cooperativos, 2020)
This paper argues that emergence of new actors such as fintech companies in the banking sector, that use intensively new technologies for the provision of financial services -many of which with disruptive solutions- are forcing traditional banking to update its business model and to place customers at the center of its activity. The structure of a new digital society is changing the relationship models between companies and users/consumers. The development of the digital economy and the collaborative economy affects both the technological processes and the form of relationship with the users of financial services. Because the customer experience is fundamental it has become the focus of attention of the fintechs as well as of the bigtechs. To analyze this digital transformation of banking, a study was carried out of the 31 main European commercial banks, using data for 2010 to 2017. The results obtained - particularly for the last years of the period - allow us to appreciate the competitive pressure exerted by fintechs on banking, which leads to the beginning of a change in thinking in many areas of banking, towards a greater focus on clients and the incorporation of the technologies that fintechs have been implementing. This process as a whole favors the democratization of financial services.
Keywords: Banking; Financial democratization; Digitalization; Fintech; Bigtech